Evaluasi Sistem Penggunaan DAK Nonfisik Kesetaraan Tahun 2021 Pada Satuan Pendidikan Nonformal Kabupaten Jembrana - G.A.P.W.P. Lestari; I.G.K.A. Sunu; I.P.W. Ariawan (Pascasarjana Universitas Pendidikan Ganesha, 2022)
This study aims to 1) find out the effectiveness of the system for using non-physical equivalent DAK for the 2021 fiscal year in Jembrana district non-formal education units in terms of the context component; 2) determine the effectiveness of the DAK utilization system in terms of input components; 3) determine the effectiveness of the DAK utilization system in terms of process components; 4) determine the effectiveness of the DAK utilization system in terms of product components; 5) determine the effectiveness of the system for using DAK together in context, input, process, product; and 6) find out the constraints in the non-physical equivalent DAK utilization system for the 2021 fiscal year in Jembrana district non-formal education units. The research was conducted at the Jembrana District Non-Formal Education Unit. This study uses a quantitative approach, this study uses an evaluation research design. The population in this study were all teaching and educational staff, totaling 20 people. The research sample was determined using a saturated sampling technique, namely the entire population. Data were collected using questionnaires, documentation, and interviews. Data analysis was performed by converting the raw score into a Z score (z-score) followed by a T score and then converted into the Glickman quadrant. The results of the study show the effectiveness of the non-physical Equivalent DAK utilization system for the 2021 fiscal year in Jembrana district non-formal education units in terms of context, the results obtained are less effective (-), the effectiveness of the DAK utilization system in terms of input, the effective results are obtained (+), the effectiveness of the DAK utilization system in terms of process effective results (+) were obtained, the effectiveness of the DAK utilization system in terms of a product obtained effective results (+). Overall, the evaluation of the context, input, process, and product variables in the DAK utilization system is classified as effective ( - + + +).